ANALISIS HUKUM TERHADAP KEBIJAKAN CORPORATE SOCIAL RESPONSIBILITY (CSR) PADA PT. BANK SUMUT - Putri Nesia Dahlius; Bismar Nasution; Suhaidi Suhaidi; Mahmul Siregar (Universitas Sumatera Utara, 2016)
ABSTRACT Corporate Social Responsibility (CSR) is a commitment of a company to participate in the suistainable economic development in order to increase the quality of life and useful environment for the company itself, for the local community, and for the people as a whole. The concept of implementing CSR in Indonesia is regulated under Law No. 40/2007 on Corporation, Law No. 25/2007 on Capital Investment, Law No. 19/2003 on BUMN, Law No. 4/2009 on Mining, Mineral, and Coal, PP (Government Regulation) No. 47/2012 on Social and Environmental Responsibility on Corporation, the Decree of the Supreme Court No. 53/PUU-XI/2008 on Constitutional Advisory of Audit Norm, under Article 74 of Law on Corporation. The result of the research showed that the implementation of CSR in Indonesia is legally obligatory, especially for a corporation, so that it is budgeted as the corporation’s expense. The policy of PT. Bank Sumut in implementing its CSR referred to Law No. 40/2007 on Corporation, PP No. 47.2012, the Decree of RUPS, and the Decree of the Director No. 240/Dir/Setdir/SK/2013 on the Operational Standard Procedure of CSR, in which Bank Sumut used CSR management with partnership pattern by collaborating with the local governmen that determined CSR planning and implementation. Key words : Corporate Social Responsibility (CSR), Law of CSR, Bank Sumut